The Situation in 2 John: A Worried Presbyter - Watt, Jan G. van der (Journal of Early Christian History, 2015)
The identity of the recipients of 2 John is much debated. Certain key issues complicate the debate, for instance, why does the presbyter mention ‘some’ of the lady's children who live in truth and not all? Who are the false teachers who claimed hospitality or at least access to the house (church)? Why are these opponents not shown the basic courtesy of inviting them into the house (church) or of even greeting them? These questions and other key issues are addressed and interrelated in order to suggest a possible scenario for the origin of the letter.
paid
Keywords: Bible. Epistle of John II – Criticism; interpretation; Bible. Johannine literature; Bultmann; Rudolf Karl; 1884-1976; Christian literature; Early; Church history – 0030-600; Hospitality – Religious aspects – Christianity; Peer reviewed